Designing context-specific bundles of innovation: Experience from WB Learning Labs - Puskur, Ranjitha; Gartaula, Hom Nath; Mukhopadhyay, Prama; Chadha, Deepali (CGIAR Initiative on Gender Equality, 2024)
Caption: This video showcases the design and implementation of context-specific socio-technical innovation bundles (STIBs) in two learning labs in West Bengal, India, aimed at empowering women farmers and enhancing their resilience to climate change impacts. Through the efforts of the EMPOWER Work Package of the CGIAR Initiative on Gender Equality, STIBs integrate local knowledge, technology, and capacity-building strategies tailored to the unique needs of women farmers. The video highlights how STIBs address climate-related challenges, promote gender equality, and contribute to building sustainable and resilient farming practices, ultimately transforming the lives of women farmers in the region.